Study on various parameters on the ibuprofen and aspirin loading with PLGA microparticles / Nur Ain Rosli Ahmad Abdullah - Rosli Ahmad Abdullah, Nur Ain (2007)
The purpose of incorporation PLGA (Poly lactic-co-glycolic acid) polymer is to prolong the action NSAIDs of choice (ibuprofen and aspirin) preparations in order to diminish the number of consumption for its analgesic effects and thus facilitate their usage. The purpose of this study was to investigate the effect of solution temperature, PY A concentration and PLGA: drug ratio on drug loading and drug entrapment efficiency. Other than that, this study also was conducted to investigate the difference in morphology of hydrophilic drug and hydrophobic drug entrap in microparticles and determine the thermal properties of microparticles with drug. The drug loading of ibuprofen and aspirin in the samples was determined through calculation of drug content percentage and drug entrapment percentage calculation. The concentration of ibuprofen and aspirin was crosscheck with UV analysis using UV spectrophotometer. The surface morphology of the samples was determined using scanning electron microscope (SEM). Thermal analysis of the PLGA microparticles and PLGA drug loaded microparticles were determined by using differential scanning calorimetry (DSC). Drug loading results show high drug loading with high ratio of PLGA used, lower solution temperature and high polyvinyl alcohol percentage as the surfactant in the microparticles preparation. Glass transition temperature of PLGA is around 52.3°C and incorporation of drug in the PLGA microparticles shifts the glass transition temperature to the right or higher temperature. Morphology of the PLGA ibuprofen loaded show spherical shape but with much lower size than PLGA drug free microparticles.